Pengembangan Teknologi Internet Of Things Pendeteksi Kebakaran untuk Ruang Server dilengkapi Pemantauan Real-Time dan Notifikasi Whatsapp Serta Monitoring menggunakan Grafana - Rizkhi, Muhammad; Syofian, Suzuki (Journal TIFDA (Technology Information and Data Analytic), 2025)
Fire is a serious threat that can cause physical, economic, and loss of life. Often triggered by human factors, nature, or equipment such as electricity and LPG, fires require rapid detection and response. Internet of Things (IoT) technology provides solutions with smart sensors that monitor the environment in real-time to detect temperature, smoke, or hazardous gases. This study develops an IoT-based fire detection system for server rooms that integrates fire sensors, MQ-2 smoke sensors, DHT-11 temperature sensors, CCTV for visual monitoring, and notification via WhatsApp. The Grafana monitoring platform is used for sensor data visualization. The case study was conducted at PT Askara Internal, with the aim of improving server room security and reducing fire risks, as well as increasing operational resilience through innovative and effective technology.